2011
DOI: 10.1111/j.1365-2664.2010.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful eradication of a non‐indigenous marine bivalve from a subtidal soft‐sediment environment

Abstract: Summary 1.Biofouling, the accumulation of biological growth on submerged surfaces such vessel hulls and artificial structures, is an important transport pathway that can facilitate the establishment of marine non-indigenous species in new locations. Despite efforts to develop effective tools to eradicate newly established populations before they become widespread and beyond control, eradication successes are scarce in the marine environment. This paper describes a dredge-based eradication of the brown mussel P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
0
24
0
1
Order By: Relevance
“…2004). The use of culling and habitat fragmentation through dredging techniques was used against the brown mussel, Perna perna (L.), and effectively reduced populations below a minimum density required for survival and reproduction (Hopkins et al. 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2004). The use of culling and habitat fragmentation through dredging techniques was used against the brown mussel, Perna perna (L.), and effectively reduced populations below a minimum density required for survival and reproduction (Hopkins et al. 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Management of the non-native plant Spartina alterniflora Loisel is thought to be optimized by the culling of plant subpopulations, effectively exploiting an Allee effect due to pollination failure . The use of culling and habitat fragmentation through dredging techniques was used against the brown mussel, Perna perna (L.), and effectively reduced populations below a minimum density required for survival and reproduction (Hopkins et al 2011). A modelling approach has suggested that culling sufficient numbers of P. carbo sinensis could led to extinction by effectively exploiting cooperative breeding behaviour (Frederiksen et al 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This history suggests that the Northern Hemisphere M. galloprovincialis on the rig originated in South Africa (into which country they were introduced in the 1960s or 1970s - Grant & Cherry, 1985), were several years old and therefore reproductively mature and were moved between NZ and Australia providing opportunity for spread into both countries. In NZ, the rig was defouled in-water by divers (Hopkins & Forrest, 2010) at which time the biosecurity threat posed by another species, the Asian green mussel (Perna viridis), was recognized and a successful programme of eradication was put in place (Hopkins et al, 2011b). However, the biosecurity threat posed by the blue mussels was not appreciated because they were not recognized at the time as Northern Hemisphere M. galloprovincialis.…”
Section: Bioinvasions Biosecurity and Management Optionsmentioning
confidence: 99%
“…As a consequence, the risk that populations of potential invaders establish themselves in recipient environments is rapidly increasing [35]. Marine invasive species may create and modify habitats, prey upon or outcompete native species, and act as either disease agents or vectors, or both.…”
Section: Introductionmentioning
confidence: 99%